The impact of hydroxychloroquine on obstetric outcomes in refractory obstetric antiphospholipid syndrome. Issue 206 (October 2021) - Gerde, M.; Ibarra, E.; Mac Kenzie, R.; Fernandez Suarez, C.; Heer, C.; Alvarez, R.; Iglesias, M.; Balparda, J.; Beruti, E.; Rubinstein, F.
Abstract: Background: The use of low-dose aspirin (LDA) and heparin has improved pregnancy outcomes in women with antiphospholipid syndrome (APS). However, 20–30% still have adverse outcomes despite treatment. Recent retrospective studies showed a beneficial effect of hydroxychloroquine (HCQ) in APS due to its anti-inflammatory, immunomodulatory and antithrombotic properties. Data in refractory obstetric APS (OAPS) remain scarce and include heterogeneous populations with various concomitant treatments. Objective: The objective of this study was to assess the impact on the obstetric outcomes of adding HCQ to classical treatments for women with refractory primary obstetric APS. Methods: In a retrospective single-centre cohort study, we compared pregnancy outcomes in women with refractory primary OAPS (2004–2019) who received two different treatments in subsequent pregnancies. Group A received 400 mg HCQ + 60 mg enoxaparin + LDA, while Group B received 60 mg enoxaparin + LDA. The main outcome was live birth rates, while pregnancy complications (early and late pregnancy losses and placental-mediated complications) were the secondary outcome. Results: A total of 101 pregnancies in 87 refractory primary OAPS patients were included. The rate of live-born babies in Group A (HCQ) was 97.1% (67/69) vs. 62.5% (20/32) in Group B (RR: 1.55 [95% CI, 1.19–2.1]; p < 0.001). Pregnancy complications in Group A were 8.7% (6/69) vs. 37.5% (12/32) in Group B (RR 0.22 [95% CI, 0.15–0.30]; p < 0.001). Conclusion: Hydroxychloroquine was associated with a higher rate of live births and a lower prevalence of pregnancy complications in refractory primary obstetric APS. The addition of HCQ to classical treatment may present a promising approach that needs to be confirmed with prospective studies. Highlights: Obstetric APS has 20–30% adverse pregnancy outcomes despite classical treatment. OAPS includes thrombotic and inflammatory pathogenic mechanisms related to aPL. Hydroxychloroquine has anti-inflammatory and antithrombotic properties. Hydroxychloroquine + enoxaparin + aspirin is associated with higher live birth rates. Adding HCQ is associated with lower pregnancy complications in refractory OAPS.